The politics of reproduction and the realities of obstetric violence in Ghana - Yalley, Abena Asefuaba (Frontiers in Global Women's Health, 2025)
IntroductionViolence during childbirth, widely conceptualized as obstetric violence, is a precarious and pressing public health concern. These include brutal acts of physical violence, humiliation, forced medical care, as well as denial of treatment. The World Health Organization recognizes it as torturous acts that put the lives of many women at risk. This paper explores the dynamics of obstetric violence through the birth narratives of women in rural and urban Ghana.MethodsQualitative phenomenological research was conducted in eight rural and urban public health facilities in the Western and Ashanti Regions of Ghana. A total of 35 women (20 from urban areas and 15 from rural areas) who had given birth in the last 24 months at health facilities were purposively selected and interviewed between August 2021 and February 2022 using a semi-structured interview guide. Thematic data analysis was conducted using the NVivo qualitative data analysis software.ResultsThe findings of the study revealed that there is a pervasive culture of violence surrounding childbirth, with women describing their childbirth memories with sadness and regret. Obstetric violence manifests in the form of physical violence, where sutures after episiotomies are performed without anesthesia, and women are beaten or slapped for their inability to push. In addition, women are grossly abandoned, usually during the second stage of labor. Sometimes, the entire care is halted when healthcare workers are provoked or feel that the women do not make enough efforts. In some cases, women are even left to deliver unassisted. Yelling, shouting, and verbal abuse of women were very dominant, and this particularly instilled fear in women, which prevented them from seeking help in critical situations, thereby increasing the risk of birth complications. Teenage mothers and HIV-positive women are predominantly discriminated against. Psychological trauma, mistrust in health institutions, and preference for unskilled birth attendants are the major consequences of obstetric violence.DiscussionOverall, obstetric violence is a major setback in Ghana's effort to achieve the global target of reduced maternal mortality. There is a critical need for the Ghanaian government to develop interventions to tackle this challenge.